2014
DOI: 10.1007/s10616-014-9767-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective propensity of Bacopa monniera against hydrogen peroxide induced oxidative damage in neuronal and lung epithelial cells

Abstract: Hydrogen peroxide (H 2 O 2 ), a major reactive oxygen species (ROS) produced during oxidative stress, is toxic to the cells. Hence, H 2 O 2 has been extensively used to study the effects of antioxidant and cytoprotective role of phytochemicals. In the present investigation H 2 O 2 was used to induce oxidative stress via ROS production within PC12 and L132 cells. Cytoprotective propensity of Bacopa monniera extract (BME) was confirmed by cell viability assays, ROS estimation, lipid peroxidation, mitochondria me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…To evaluate neuroprotective property of bacoside A components and mixture against stress in neuronal cells, H 2 O 2 was used as an oxidant to induce oxidative stress on N2a neuroblastoma cells. Previous studies have reported that H 2 O 2 is known to induce oxidative stress that cause lipid peroxidation, ROS generation, GSH depletion and reduction in mitochondrial membrane potential (MMP), antioxidant enzymes (SOD, catalase and GPx) activity . This oxidative stress was observed to be associated with increase in intracellular ROS .…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…To evaluate neuroprotective property of bacoside A components and mixture against stress in neuronal cells, H 2 O 2 was used as an oxidant to induce oxidative stress on N2a neuroblastoma cells. Previous studies have reported that H 2 O 2 is known to induce oxidative stress that cause lipid peroxidation, ROS generation, GSH depletion and reduction in mitochondrial membrane potential (MMP), antioxidant enzymes (SOD, catalase and GPx) activity . This oxidative stress was observed to be associated with increase in intracellular ROS .…”
Section: Discussionmentioning
confidence: 72%
“…superoxide dismutase, catalase and glutathione peroxidases in the neuronal cells . Bacosides‐rich extracts were evaluated for their anti‐apoptotic and cytoprotective properties on neuronal and lung epithelial cell lines . Existing studies had provided extensive documents on nootropic properties of B. monnieri but lack information on the role of four different bacoside A components in alleviating progression of neuronal diseases .…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations